Solution of the Inverse Problem of Subsurface Electric Exploration for Horizontally Stratified Medium. (20th November 2013) - Karchevsky, A. L.; Oralbekova, Zh. O.; Iskakov, K. T.
Abstract : In this paper, we offer the generalization of the known technique of the construction of the gradient of the residual functional based on the statement of the conjugate problem for the case when the unknown function is complex valued. The notion of the reference frequency of the medium is introduced. Knowing the value of the reference frequency lets us judge the possibility of simultaneous definition of the dielectric permittivity and conductivity.